Relación entre las exportaciones y el valor agregado bruto de Loreto, período 2017 - 2021 - Curimania Quiroz, Luis Angel (2024)
Loreto's exports have historically been based on activities that exploit natural resources. The purpose of this study is to determine the relationship between exports and gross value added in Loreto, during the period 2017 to 2021, for which a Correlational scope and Non-Experimental design was used, composed of traditional and non-traditional products, and the gross value added, composed of eleven economic activities, calculated at constant prices. From the analysis of exports, the traditional product “Crude oil and derivatives” had the highest concentration during the analysis period, which was US$277.109 million, representing 84.79% of total exports. For its part, the economic activity with the highest concentration is the “Extraction of oil, gas and minerals”, with a contribution of S/ 7,370,567.00, representing 59.33% of the total production of the series studied. Concluding in the non-existence of a direct relationship between exports and regional production from 2017 to 2021, since the Pearson coefficient was 0.781260161; far from 1, determining that there is no good relationship between the analyzed variables; Likewise, the result of the coefficient of determination (R2) = 0.610367439, which is less than 0.70, indicates that exports cannot determine the trajectory of regional production in Loreto.